2005
DOI: 10.2174/1568010053622911
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenesis for Rheumatoid Arthritis

Abstract: Angiogenesis, i.e., the induction of new blood vessels from existing vasculature, is a crucial event in the formation and maintenance of the pannus in rheumatoid arthritis (RA). The arthritis is characterized by destruction of peripheral joints in which the cartilage and bone are destroyed by proliferative synovitis. This is characterized by infiltration of inflammatory cells and formation of new blood vessels. Angiogenesis occurs since the early stage of the disease, and supports progression of the arthritis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…This is characterized by infiltration of inflammatory cells and formation of new blood vessels. Angiogenesis occurs since the early stage of the disease, and supports progression of the arthritis (Roccaro et al, 2005). The results in this paper demonstrated that inflammation inhibitors may have the potential to be the angiogenesis inhibitors because the anti-inflammatory traditional botanical Tripterygium wilfordii and its terpenoids, triptolide and celastrol, also showed potent antiangiogenic activity in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 67%
“…This is characterized by infiltration of inflammatory cells and formation of new blood vessels. Angiogenesis occurs since the early stage of the disease, and supports progression of the arthritis (Roccaro et al, 2005). The results in this paper demonstrated that inflammation inhibitors may have the potential to be the angiogenesis inhibitors because the anti-inflammatory traditional botanical Tripterygium wilfordii and its terpenoids, triptolide and celastrol, also showed potent antiangiogenic activity in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 67%
“…Elevated levels of VEGF were found in rheumatoid arthritis patients, and administration of soluble VEGFR-1 attenuated the disease process in an animal model of rheumatoid arthritis (49). Increased VEGF levels have also been reported in polycystic ovary syndrome, one of the leading causes of female infertility (50).…”
Section: Vegf Signaling and Disease-therapeutic Approachesmentioning
confidence: 95%
“…Elevated levels of VEGF were found in rheumatoid arthritis patients, and administration of soluble VEGFR-1 attenuated the disease process in an animal model of rheumatoid arthritis (49). Increased VEGF levels have also been reported in polycystic ovary syndrome, one of the leading causes of female infertility (50).…”
Section: Vegf Signaling and Diseaseötherapeutic Approachesmentioning
confidence: 98%